International graduates and the change of initial career mobility intentions. Issue 4 (13th May 2019) - Farivar, Farveh; Coffey, Jane; Cameron, Roslyn
Abstract : Purpose: The purpose of this paper is to investigate which sociocultural and work conditions have the potential to change international graduates' career mobility intentions and encourage international graduates to stay in the host country when the initial intention was to leave the host country after graduating. Design/methodology/approach: Data were collected via a web-based survey from international graduates and analyses suggest 129 (20 percent) of respondents changed their initial career mobility intentions. Data were analyzed using fuzzy-set qualitative comparative analysis. Findings: Although previous studies report some pull–push factors such as attractive payment rates and work experience as being important in attracting potential workforce participants, these factors have no influence on changing the career mobility intentions of international graduates. In contrast, the work environment (WE) seems to be a strong condition for changing career mobility decisions. Results also reveal that the influence of sociocultural conditions on initial career mobility intention is more complicated than work conditions and varies from case to case. Practical implications: The present study adopts the theoretical assumption that migration and mobility is a transition that forms over time and the findings suggest that international graduates' global career mobility intentions depend on the WE. Therefore, government, higher education and industry development policy makers need to take this factor into account if they are interested in attracting and retaining global talent. Originality/value: The majority of previous studies have focused on which push–pull factors encourage the recently graduated international student workforce to move or stay in a country while the current study argues which conditions have the potential to change initial career mobility intentions.